ANALISIS PEMANFAATAN MANGROVE OLEH MASYARAKAT PESISIR DAN PERTISIPASINYA TERHADAP PELESTARIAN MANGROVE DI GAMPONG KUALA BUBON - Ika Kusumawati; Neneng Marlian; Maria Ulfa (Universitas Teuku Umar, 2019)
The use of mangrove forests in Kuala Bubon, in general, gives priority to economic functions rather than ecological functions. If this is not managed as soon as possible, damage to mangrove forests will become more extensive. In general, there are two factors causing damage to the mangrove forests that occurred in the Kuala Bubon, namely human factors and natural factors. The objective of this study is to determine the use of mangrove forests for the life of coastal communities and the participation of communities in the preservation of mangroves. The method of data collection using survey methods is carried out from descriptive and quantitative way. Perception and community participation were analyzed using quantitative descriptive methods. The method used to measure people's perception is the Likert scale method. The results of the study showed that the use of mangroves for the life of coastal communities was still in the middle category, based on the categorization of the data, revealed that the value of using the mangrove (1,113) is one of the criteria that approaches high levels. This shows that the use of mangroves in the village of Kuala Bubon, Samatiga district, West Aceh Regency is already good, although there is still no specific sanction for people who cut illegally. Community participation in the conservation of mangroves can improve the lives of coastal communities is still insufficient when, based on the calculation of the categorization of data obtained, the value of the community participation of 1,498 is among the average criteria.